Dewatering of sludge by freezing - Franceschini, Ottavio (2010)
The aim and scope of the project is to study a freezing and thawing apparatus developed by FriGeo AB, company located in Kiruna, in order to enhance the deliquorability of workshop sludges collected from the airport of Arlanda, Stockholm, and other minor sources. Two sludges with different initial characteristics have been analysed. The first sludge (S1) had the following composition: 60 wt% water content, 28 wt% organic matter (oil plus organic substances), and 12 wt% inorganic material (principally fine- grained material). The second sludge (S2) underwent to different pre- treatments to remove part of its water and oil content: 35 wt% water content, 11 wt% organic matter and 54 wt% inorganic material (principally coarse-grained material). Despite the different inorganic composition, the fine-grained material of both the sludges had a similar grain size distribution. The principal internal characteristics and external conditions that influence the dewatering and consolidation of sludges and soils when frozen and thawed have been researched in literature: sludges consolidation is principally enhanced by slow freezing rate (obtained with indirect freezing method at low temperature): while the ice front is moving, the sludge particles are compacted and the oil droplets coalesce, resulting in higher deliquorability while thawing. This effect becomes negligible with high concentration of dissolved substances, salts and impurities. The compaction of soils depends principally on their grain size distribution: three freezing/thawing cycles allow the fine-grained material to reach its maximum compaction: impurities, fast freezing and fast thawing rate contrast this effect. The most suitable parameters among freezing temperature and number of freezing cycles have been chosen varying their values, with the aim to obtain the best deliquorability degree. Soil tubes containing 300 ml of sludge have been placed into a laboratory freezer: 1, 3 or 5 freezing cycles at 5, 10, 20 and 28°C have been performed: the freezing time ...